New Assessments, Better Instruction? Designing Assessment Systems to Promote Instructional Improvement - Faxon-Mills, Susannah (RAND Corporation, 2013)
This report reviews the literature on how assessment affects teaching practice and the conditions that moderate that relationship. The authors identify a wide variety of effects that testing might have on teachers' activities in the classroom and a number of conditions that affect the impact that assessment may have on practice.